Formulation and Evaluation of Mangosteen (Garcinia mangostana L.) Fruit Pericarp Extract Gel - Kuswahyuning, Rina; Lesmana, Indra (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2021)
The topical antioxidant product may be useful for the treatment of oxidative stress-related skin disorder. This research aimed to evaluate a topical gel formulation of Garcinia mangostana L. fruit pericarp (GMP) extract. GMP extract was formulated into a gel and characterized for its physical properties. The antioxidant activity was evaluated based on the radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity. The ability of gel formulation to release GMP extract and promote skin delivery was estimated based on DPPH scavenging method and also compared to that of suspension form. The results showed that the GMP extract gel showed characteristics for topical application. The radical DPPH scavenging activity was confirmed both in GMP extract and GMP extract gel. In vitro study release showed that the GMP extract was released from gel. Some degree of GMP extract was also delivered into the shed snakeskin in vitro. When compared with the suspension form, GMP extract gel provided a more profoundly lower release.